Jane [videorecording (DVD)] - Petsch, Madelaine, 1994-; Leo, Melissa; Medders, Kerri (Breaking Glass Pictures, 2023)
When Olivia is deferred from her dream college she begins to spiral. To regain control, she embarks on a social media war against those in her way, but as things escalate, she is forced to embrace her darkest impulses to get ahead.